Um estudo em livros didáticos sobre as contextualizações e o método resolutivo das equações quadráticas - COSTA, Bruna Pires (Universidade Federal do Tocantins, 2023)
This work presents a study carried out in Mathematics Textbooks (DL) about the contextualization of Quadratic Equations. The guiding question was expressed in the following terms: How is the resolution of high school polynomial equations contextualized in textbooks? The general objective was to analyze the exercises on polynomial equations of the second degree, and verify the explored contextualizations. This study used bibliographical research, which enabled a contact with materials already available, such as textbooks for teachers. Three Mathematics books from the first year of High School from different collections were analyzed, namely: Conexões com a Mathematics; Mathematics: Context & Applications and Mathematics: Interaction and technology, which received a simplifying nomenclature respectively denoted by L1, L2 and L3. As a result of the research, the identification and exploration of three areas used for the contextualization of the equations of the second degree stand out, which are Physics, Civil Engineering and Economics, as well as the importance of introducing applicability and contextualization of the activities/exercises of the equations quadratics for the student's mathematical training.